A Pastoral do Turismo e sua ambiguidade estrutural - Moreno, Pedro Augusto Ceregatti (2016)
Recognized by the World Tourism Organization (WTO) as a share of this market, religious tourism provides significant revenue and traffic people, nationally and internationally. Its expansion has come about in Brazil as recognition of their earning potential. It’s results of transition from a phase in which the pilgrimages and festivals did not happen spontaneously and management for the current state of business structuring and training of its staff and services provided. Several factors are intertwined in the development of this market in Brazil, and the government agencies responsible for most of the investments in the sector. They promote infrastructure improvements and incentive programs focused on events and religious attraction poles, thereby providing enhancement of the hotel chain, transport connection, agencies and tour operators. The Catholic Church is mobilizing to that particular field, with its Pastur focused on the dissemination of shrines and religious appeal sites, staff training and strategies that promote the sale of travel and tourism practices packages Dioceses and parishes with potential attraction. This work exposes the one hand, economically enterprising character of the church and on the other, the ambiguity of the Pastur, as the pastoral intended for non-profit activities. Here is the facet of Brazilian Catholicism to which this research is back.